HKBP HIV-AIDS Committee Balige Coordination with the Regional Government HIV-AIDS Handling Program in Toba Samosir Regency 2018 - Tambunan, Martinus S; Aulia, Destanul; Rochadi, Kintoko (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The increase in the number of HIV-AIDS cases in the last ten years from 2008 to 2017 in Toba Samosir Regency with an average HIV growth of â‰¥ 7% and AIDS growth of â‰¥ 31%, has to be handled by implementing a special program. The lack of coordination between HKBP AIDS Committee Balige and Regional Government has to be made since there is no similar opinion about HIV-AIDS, the government agencies which are joined in the Committee of Regional AIDS Handling are not focused on prioritizing HIV- AIDS problems, and coordination in planning has not been optimal so that the budget is limited. The objective of the research was to find out the coordination between HKBP AIDS Committee, Balige and the Regional Government in HIV-AIDS Handling program in Toba Samosir Regency. The research used qualitative method (phenomenology design) which was aimed to get information about the coordination in preventing and handling HIV-AIDS in Toba Samosir Regency, with 20 informants. The data were gathered by conducting in-depth interviews and documentary study and analyzed by using content analysis. The result of the research showed that coordination, involvement, and active participation of all agencies in the KPAD (Regional AIDS Handling Committee), the implementation of budget planning, and activity planning were inadequate. It is recommended that formal meetings be increased in order to develop communication and to create good coordination, either from budget planning or from the implementation of handling HIV-AIDS in Toba Samosir Regency.Â